Graphene Quantum Dots Supported Mo3S4 as a Promising Candidate for Pt-Free Counter Electrode in Dye-Sensitized Solar Cell and Supercapacitor Applications. (7th September 2021) - Gayathri, V.; Peter, I. John; C., Raja Mohan
Abstract : We have synthesized with and without graphene quantum dots (GQDs) supported Molybdenum sulfide (Mo3 S4 /GQDs) by the hydrothermal route and examined the effect on electrochemical and dye sensitized solar cells (DSSCs) performance. The crystalline structure and composition are elucidated by X-ray diffraction and X-ray photoelectron spectroscopy, respectively. The synthesized samples show a spherical nature which is confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). JV spectra reveal GQDs modified Mo3 S4 counter electrodes deliver the highest short circuit current ( J SC ) of 13.84 mA cm −2, open-circuit voltage ( V OC ) of 0.72 V, and power conversion efficiency (PCE) of 5.67%, which is 13% higher compared to pristine counter electrodes. Low peak to peak separation ( Epp ) and higher peak current density ( Jpc ) and exchange current density ( Jo ) are responsible for this improvement. Besides, the samples have been employed as a working electrode and studied supercapacitor performance. Among them, Mo3 S4 /GQDs exhibited the highest specific capacitance of 234 F g −1 at 2 A g −1 . The results mentioned above reveal GQDs supported Mo3 S4 is not only a viable substitute for Pt-free counter electrodes but also provide a better outlook for energy storage devices.